Income inequality among the social classes in the U.S. since the great recession 2008 and its causes = Bất bình đẳng thu nhập giữa các tầng lớp xã hội Mỹ từ sau khủng hoảng kinh tế 2008 và nguyên nhân của vấn đề - Ngô, Thị Trang (2020)
Shiller (2013), Nobel-winning economist, has stated that rising inequality in the United States and elsewhere is among the most important problems that Americans have to deal with today. In reality, the onward trend towards unequal income distribution has existed in the U.S. for a long time; however, after the Great Recession 2008, the issue has become significant when income gap among the classes, especially the gap between the top 1 percent and the bottom 99 percent, was at the highest level. The thesis aims to answer the question how have trend and level of income inequality developed and caught concern of the U.S. society since the Great Recession 2008 and find the root causes of the issue. To conduct the thesis, two research methods: data analysis and content analysis are adopted to employ statistics, articles, reports and studies. Thesis’s findings have shown the massive gap between the highest and the lowest income group when top ten percent alone takes around 50 % total income proportion. In this situation, surveys were carried out to evaluate American responses to see how important income inequality is and whether American society feel satisfied with that. The change in technology, resulting in “skill-biased technological change” which prefers skilled workers in production process and larger profits for the owners, is considered one of the driving causes of the U.S. income gap. Moreover, international trade openness and immigration- both related to globalization are among the triggers of the issue. Finally, government’s policies, specifically tax cuts under Reagan’s and Bush’s years, are contributing factors to worsen income gap.